The effects of filler loading and coupling agents on properties of recycled high density polyethylene / wood fiber composites - Mohd Hanif Mohd Pisal (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
The recycled high density polyethylene (rHDPE)/wood fiber (WF) composites had been prepared using BrabenderPlasticorder at temperature 160C with rotor speed of 50 rpm. The effect of wood fiber loading and coupling agents on tensile properties, water absorption, morphology, spectroscopy infrared (FTIR) analysis, thermogravimetric analysis(TGA) and x-ray diffraction (XRD) of rHDPE/WF composites were investigated.